Improvement of critical current density in Sb-doped HgBa2Ca2Cu3O8+delta superconductor prepared by Hg vapour diffusion process - Li, J; Lam, C; Abell, J; Peacock, G; Edwards, P; Shen, L (1999)
Antimony-doped Hg-1223 superconductors have been synthesised from the reaction of a Sb-doped precursor with elemental Hg vapour released from a reactant in sealed silica tubes (the Hg vapour diffusion process). The Hg vapour pressure can be controlled by a small addition of Se in the reactant bars. The phase purity and micro structure of the material have been characterised by XRD and SEM and the superconducing properties measured by electrical resistance and AC susceptibility. High quality superconducting material can be fabricated by this Hg vapour diffusion process with a suitable Se addition in the reactant bars. The micro structure reveals dense, plate-like grains with reduced void formation, when compared with material prepared by a solid state reaction route. Resistance and AC susceptibility measurements give a Tc of 132 K. The diffusion process route significantly enhances the intergrain critical current density (Jc = 2.5 X 107 Am-2 at 77 K and zero field) and reduces the degradation of Jc in a magnetic field. © 1999 Elsevier Science B.V. All rights reserved.